Morphological variation in the redfish (Sebastes spp.) complex in Norwegian waters - Bruvold, Ingrid Marie (UiT Norges arktiske universitet, 2021)
The golden redfish Sebastes norvegicus is a long-lived commercial species of redfish in the North Atlantic. Excessive harvest through decades has led to a decline in the mature population in Norwegian waters, which is currently considered to be severely depleted. Accumulating genetic evidence suggest a more complex structure within the Sebastes genus in the North Atlantic, which has recently formed a hypothesis of a cryptic species complex among S. norvegicus represented by the two types A and B. Despite apparent genetic divergence between the types, they have yet to be described morphologically. The external morphology of genetically identified whole fish from Norwegian and East Greenland waters was investigated using traditional morphometric methods to identify descriptive characters for delimitation, applying linear discriminant analysis and random forest classification procedures for extraction of shape information. Combined with non-parametric meristic analysis, the results suggest that features such as beak length and eye orbit size provide good discrimination between the proposed cryptic species as well as separating them from S. mentella and S. viviparus. Analyzing growth patterns of the proposed cryptic species did not explain previous findings of two distinct growth trajectories among S. norvegicus in Norwegian waters, but indicated that they do not possess equal potential for maximum growth. These findings support the hypothesized existence of a species complex in Norwegian waters which can be distinguished both with morphological and genetic analysis, and should be considered in development of monitoring and management strategies further on.